2000
DOI: 10.1021/jf000141k
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Oxytetracycline, Tetracycline, and Chlortetracycline and Their Distribution in Egg White, Egg Yolk, and Hen Plasma

Abstract: 4-epioxytetracycline and N-demethyloxytetracycline, as metabolites of oxytetracycline (OTC), 4-epitetracycline and N-demethyltetracycline, as metabolites of tetracycline (TC), and 4-epichlortetracycline, isochlortetracycline (ICTC), 4-epi-ICTC, and N-demethyl-ICTC, as metabolites of chlortetracycline (CTC), were detected in egg yolk and plasma obtained from feeding studies with either OTC, TC, or CTC. In egg white, only OTC, TC with its 4-epimer, and ICTC with its 4-epimer were detected in substantial concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…They found that the drugs were present in greater amounts in the egg yolk than in the white and also remained for longer in the yolk. Vandenberge et al (2012) and Zurhelle, Petz, Mueller-Seitz, and Siewert (2000) also reported similar results. Further, Alaboudi, Bash, and Musallam (2013) reported finding higher concentrations of chlortetracycline in egg white than in yolk.…”
Section: Toxicology and Chemical Food Safetysupporting
confidence: 64%
See 1 more Smart Citation
“…They found that the drugs were present in greater amounts in the egg yolk than in the white and also remained for longer in the yolk. Vandenberge et al (2012) and Zurhelle, Petz, Mueller-Seitz, and Siewert (2000) also reported similar results. Further, Alaboudi, Bash, and Musallam (2013) reported finding higher concentrations of chlortetracycline in egg white than in yolk.…”
Section: Toxicology and Chemical Food Safetysupporting
confidence: 64%
“…Vandenberge et al. () and Zurhelle, Petz, Mueller‐Seitz, and Siewert () also reported similar results. Further, Alaboudi, Bash, and Musallam () reported finding higher concentrations of chlortetracycline in egg white than in yolk.…”
Section: Resultsmentioning
confidence: 59%
“…When administrated to layer chickens, drug residues appear more firstly in albumen than in yolk egg but concentrations could reach higher levels and persist in yolk [36][37][38][39]. During the present study, albumen and yolk egg were not separated during screening process and this could be the reason of the weak level of tetracycline residues in eggs tested.…”
Section: Screening Of β-Lactam and Tetracycline Residues In Tissue Anmentioning
confidence: 72%
“…Previous results showed that oxytetracycline breaks down to several metabolites, including 4-epi-oxytetracycline. For example, 4-epi-oxytetracycline and N-demethyloxytetracycline were detected as metabolites of oxytetracycline in egg and hen plasma [11]. In another study, 4-epioxytetracycline was also detected in bones (femur, breastbone, fibula, and tibia) from broilers treated with oxytetracycline [12].…”
Section: Discussionmentioning
confidence: 96%